AB0323 Persistence of Biologic Therapy and Long Term Outcomes at 14 Years: Observational Data in Patients with Rheumatoid Arthritis from A Single Centre. (15th July 2016) - Fernandes, M.A.; Figueiredo, I.; Riso, N.; Panarra, A.; Moraes-Fontes, M.F.
Abstract : Background: Current recommendations for Rheumatoid Arthritis (RA) treatment focus on a treat to target approach [1, 2]. Long term individual drug persistence has been associated to factors such as type of biological agent and higher disease activity [3, 4]. Here we present data from a tertiary referral centre. Objectives: To determine factors associated to drug persistence, switch or withdrawal of first-line biological therapy. Methods: Retrospectively collected data (01/2002 to 12/2015) from our Unit included patients classified as RA according to ACR 1987 [5] and 2010 [6] criteria. The analysis included 288 patients, 29% (n=85) of which were lost to follow-up and 15% (n=44) of which were deceased. The present study was restricted to current biological therapy. We extracted baseline characteristics (age, gender, presence of RF and anti-CCP, duration of RA, year of initiation of therapy), first biologic and causes of switch or withdrawal, adverse events and treatment efficacy (according to DAS28). Data were collected through to December 2015. Outcomes were compared using the Man-Whitney test comparing those that maintained the same biologic to those that switched. We limited the analysis to patients treated with Etanercept (ETN), Adalimumab (ADA), Rituximab (RTX) and Tocilizumab (TCZ). Results: A total of 85 patients (53%) were started on biological therapy (bDMARD), instituted after methotrexate (MTX) failure or intolerance (mean peak MTX dose 17 mg/week). Mean age [±SD]=59 [±10.2] years, 79% female (n=65), mean disease duration 11.3 [±7.2] years (ranging from 1 to 37 years), 6 (7%) non-white, the majority positive for rheumatoid factor and/or anti-CCP (n=61, 72%). These patients were originally treated with ETN (n=56), Infliximab – INFLIX (n=3), ADA (n=12), RTX (n=6), TCZ (n=7) and Golimumab (n=1) (Graph I). After mean 4 [±2.9 [±SD] years of follow-up, ranging from 1 to 14 years (Graph II), 70 of 85 patients are currently still on bDMARD, mostly on ETN (n=34), TCZ (n=13), RTX (n=11) and ADA (n=9). Abatacept has been started on one patient. The median time of receiving ETN, ADA, RTX and TCZ was 5.0, 3.5, 2.0 and 4.0 years and retention rates were 71%, 67%, 83% and 86%, respectively. Overall, more than 95% of treatment switch was due to drug inefficacy. Severe infections occurred with ETN (one Pneumocystis pneumonia) and ADA (one genitourinary tuberculosis). Lack of efficacy due to TCZ was only seen in a single patient. There was no statistically significant differences between retention and non-retention groups. Conclusions: Biological drugs for RA treatment in our Unit were determined by drug development and National Authority of Medicines and Health Products authorization. ETN was the most frequently used and for the longest duration with a 71% retention rate. Overall we found that the other agents were also well tolerated and effective in patients between 50 and 70 years of age. This information may be useful for clinicians with an ageing population. References: Singh Arthritis Care Res (Hoboken), 2015; Smolen Ann Rheum Dis, 2014; Favalli Arthritis Care Res (Hoboken), 2015; Frazier-Mironer Joint Bone Spine, 2014; Arnett Arthritis Rheum, 1988; Aletaha Arthritis Rheum, 2010. Acknowledgement: Patients, Medical, Nursing and Administrative Staff of Unidade de Doenças Auto-imunes, Hospital Curry Cabral Disclosure of Interest: M. Fernandes: None declared, I. Figueiredo: None declared, N. Riso: None declared, A. Panarra: None declared, M. F. Moraes-Fontes Grant/research support from: Roche, AbbVie, Pfizer, Biomarin, Actelion, Consultant for: Pfizer